Taxpayer compliance analysis on micro, small and medium business in Surabaya - Karolina Setia; Aloisius Hama (Junal Ilmu Manajemen, 2023)
Governmental expectations to all taxpayers concerning payment of its ease can pay for release without there is insincerity. Society has to pay for release truly as according to law and regulation going into effect but in reality faced many resistance in imposition execution, the taxpayer do not master correctness about taxation law and sanctions to accept the effect of deviation of ease so that on duty taxation assume the mentioned as non-compliance and give pressure, sanction. The object in this research is a small industrial company in Surabaya. utilized by Type Data is the primary data stem from a questionnaire which has been filled in by the owner / company manager with the amount taken by a sample of 30 small industrial companies. Analysis method use doubled linear regression method. The results of the research can be concluded that social pressure, sanction perception and understanding of taxpayers have an effect on by partial and simultaneous compliance of dominant factors and taxpayers have an effect on compliance of taxpayers is the understanding of law tax payer of taxation.